From Information to Knowledge: Business Intelligence Usage and Perspectives - Damir Ravlić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
A lack of quality data is one of the managing problems. It does not mean that they do not exist, but on the contrary, we are usually swamped with unnecessary information. The problem is how to extract the essential data for decision-making from the large amount of data. The data are the part of the organization's assets and, together with the capital and human resources, are an important part of the overall competitiveness. New technologies to support taking the correct and valid conclusions from the "enormous" amounts of data are created every day. Business intelligence and knowledge management are indispensable elements of successful business systems and public administration strategy. The concept of business intelligence or business information management is one of the modern systems that offered the possibility of a comprehensive and efficient usage of information. The concept of business information management also provides usage of the remaining collected data and converting them into useful information and knowledge. The information technology development in recent years provides the ability to store large amounts of information at lower costs, and people share their knowledge and jointly and interactively work at large distances. If we take into account the aspirations of Bosnia and Herzegovina toward accession to the EU, the concept of business intelligence is even more important as our systems can be connected with the systems at the European Union level, or the public administration interoperability in the European context can be achieved. Goal of the paper is to review the notion of business intelligence, and to assess the level of business intelligence usage in the public organizations in Bosnia and Herzegovina.
Keywords: O31; D83; 330; business intelligence; information; knowledge; Bosnia and Herzegovina; public organizations